2011
DOI: 10.1111/j.1600-0501.2010.02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Early and immediate loading of titanium implants with fluoride‐modified surfaces: results of 5‐year prospective study

Abstract: Implants used in this study had high survival and success rates after 5 years. Marginal bone was well maintained, irrespective of the loading regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 22 publications
2
50
0
4
Order By: Relevance
“…15,16,[42][43][44][45] In this study, 4 early implant failures occurred and one implant rotated at 5 weeks post-surgery. The results are in agreement with those from several other studies as reported in a recent review on the outcomes of micro-rough surface Straumann 6 mm implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16,[42][43][44][45] In this study, 4 early implant failures occurred and one implant rotated at 5 weeks post-surgery. The results are in agreement with those from several other studies as reported in a recent review on the outcomes of micro-rough surface Straumann 6 mm implants.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have confirmed that using early loading protocols for dental implants can have high survival rates and good clinical outcomes. [14][15][16][17][18] However, whether the early loading protocol can be used routinely remains unclear. This is particularly so in the posterior jaws, where the occlusal forces are much higher than in the anterior jaws; or with the short implants, which have less part engaged in bone.…”
mentioning
confidence: 99%
“…Aunque, al comienzo de la implantología oral se preconizaba un tiempo de cicatrización libre de carga funcional de 3-6 meses, de hecho, en la actualidad la carga precoz representa un avance en el desarrollo de los protocolos implantológicos, ya que al reducir el tiempo de espera, beneficia a los pacientes con diferentes pérdidas dentales (12)(13)(14)(15). Los protocolos de carga precoz se han desarrollado porque han mejorado los aspectos quirúrgicos de los implantes.…”
Section: Discussionunclassified
“…: arenado y grabado ácido) favorece la oseointegración y reduce el tiempo de cicatrización, lo que posibilita la carga precoz de los implantes mediante la correspondiente restauración prostodóncica (11)(12)(13)(14)(15).…”
Section: Introductionunclassified
“…20,21,23,[26][27][28][29][30] İmmediyat yüklenen implantlar hastaların yaşam kalitesi üzerine olumlu etki yapabilir, çalışma-larda immediyat yükleme protokolünün hastaların yaşam kalitesini artırdığı rapor edilmiştir. 7,23,[31][32][33][34][35][36][37][38][39][40] …”
Section: All On Four Ve Benzer Sistemler Ile;kemikunclassified